The Impact of Budgetary Participation on Task Performance in Government Agencies: How Innovative Behavior Mediates the Relationship - Akhsanul Khaq; Suwarno Suwarno; Tanusree Chakravarty Mukherjee; Ting Qian Hui (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Good budget planning enables the government to effectively establish priority scales and avoid overlapping programs between agencies. One crucial element in this process is budget participation, which not only strengthens employees' sense of ownership, responsibility, and commitment to organizational goals but also contributes to the efficiency of program implementation. This study aims to analyze the effect of budget participation and innovative behavior on task performance among civil servants in public sector in Jakarta, Indonesia. The research adopts a quantitative approach using a Likert scale questionnaire (1–7), distributed to 188 civil servants’ respondents selected through a simple random sampling technique. The collected data were analyzed using the Structural Equation Modeling (SEM) method with the help of SmartPLS 3 software. The results indicate that budget participation has a positive and significant effect on both innovative behavior and task performance. Furthermore, innovative behavior was found to mediate the relationship between budget participation and task performance, indicating that an innovative culture enhances the effectiveness of budget implementation in achieving performance targets. This research provides practical contributions in supporting bureaucratic reform and improving the quality of public services.